(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to identify (the effect of the Tragist model on the collection of Arabic grammar among first-grade female students).The current research is determined by a sample of intermediate first-grade students in intermediate and secondary day schools affiliated to the General Directorate of Education of Rusafa / the second in Baghdad Governorate, and the topics of the Arabic grammar book to be taught to intermediate first-grade students in Iraq for the first semester of the year 2012-2013 AD.The researcher followed the experimental design with partial control as a research design, and the research community consisted of secondary and intermediate day schools for girls in the General Directorate of Education of Rusafa / the second in Baghdad.